French military general practitioner: ultrasound practice. Issue 3 (31st July 2013) - Maurin, Olga; De Regloix, S; Lefort, H; Delort, G; Domanski, L; Tourtier, J-P; Palmier, B
Abstract : Objectives: Ultrasound has been used in the field and in emergency departments for more than two decades. In a military setting, its use has grown rapidly as it has gained widespread acceptance among emergency physicians and as the range of diagnostic and triage applications has continued to expand. Technological changes have enabled ultrasound devices to become accessible to general practitioners (GP), and it could be of particular interest for military GPs in isolated environments. We have investigated both the training of French military GPs in the area of ultrasonography and the use of ultrasound devices, in daily practice and abroad, in isolated military settings. Methods: In 2011, a questionnaire was sent to all 147 in-the-field GPs of the French southeast regional military health service. The questionnaire evaluated the training of military GPs in ultrasonography, the use of ultrasound in France in daily practice, and during military operations in isolated environments abroad during 2010. Results: The response rate was 52%. On the one hand, half the responding GPs had been specially trained in ultrasound, mainly (97%) in military institutes. On the other hand, only a quarter of doctors used ultrasound in daily practice. Among those GPs performing ultrasound examinations in France, 75% used it in 2010 during isolated operations abroad. Ultrasound examinations performed in such an austere environment were retrospectively declared useful to guide clinical reasoning (41% of examinations carried out), diagnosis (21%) and decision making as regards evacuation (11%). Conclusions: The challenge for the future is to make ultrasound courses mandatory for all military GPs going on overseas operations, to develop daily practice, and to investigate effective triage systems, combining both ultrasound imagery and physical examination.